Comparison of Bcl-xL protein expression in placental trophoblast cells between pregnancy complicated by severe preeclampsia and normotensive pregnancy - Diah Rumekti Hadiati; Arsi Palupi; Mohammad Hakimi; Sofia Mubarika Haryana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Preeclampsia is one of the main causes of maternal and perinatal mortality and morbidity.The pathogenesis of preeclampsia remains unclear until now. It is believed thatregulation of apoptosis in trophoblast cells plays an important role in the pathophysiologyof preeclampsia. Failure of spiral arteries remodeling will eventually lead to placentalhypoxia lead to excessive trophoblast apoptosis. The molecular mechanism of apoptosisis very complicated involving many signaling molecules included Bcl-2 proteins. The Bcl-2 protein group consists of proapoptosis proteins (Bax) and apoptosis inhibitor proteins(Bcl-2 and Bcl-xL). The aimed of this stuty was to compare the expression of Bcl-xLprotein in placental trophoblast cells of pregnancy complicated by severe preeclampsiawith that normotensive pregnancy. This study was an observational study with crosssectional design involving 43 pregnancy patients with severe preeclampsia and 38normotensive pregnancy who treated in Dr. Sardjito General Hospital, Yogyakarta fromOctober 2011 until March 2012. Placenta samples were obtained from all subjects forBcl-xL protein expression analysis using immunohistochemistry technique. Data wereanalyzed using independent t-test, chi-square test, and logistic regression. A p value<0.05 was considered significant. Significant difference in Bcl-xL protein expressionin trophoblast cells of pregnancy complicated by severe preeclampsia (1.29 ± 0.12)compared to that normotensive pregnancy (1.71 ± 0.14) was reported (p = 0.00). Inaddition, logistic regression test showed that diagnosis of severe preeclampsia had astatistically significant role in Bcl-xL protein expression (p= 0.000). In conclusion, theexpression of Bcl-xL protein is lower in pregnancy complicated by severe preeclampsiacompared to normotensive pregnancy.